Ticagrelor Is Superior to Clopidogrel in Inhibiting Platelet Reactivity in Patients With Minor Stroke or TIA - Yang, Yingying; Chen, Weiqi; Pan, Yuesong; Yan, Hongyi; Meng, Xia; Liu, Liping; Wang, Yongjun; Wang, Yilong (Frontiers in Neurology, 2020)
Background: The combination of clopidogrel and aspirin is recommended for the treatment of patients with acute minor stroke or transient ischemic attack (TIA). However, with varied clopidogrel resistance (often due to CYP2C19 loss-of-function (LOF) alleles), alternatives like ticagrelor have been suggested. Previous studies showed that ticagrelor had a lower platelet reactivity assessed by VerifyNow P2Y12 assay than clopidogrel. We aimed to compare the effect of ticagrelor versus clopidogrel on platelet reactivity assessed by a different method (Aggrestar platelet function analyzer) and analyze whether CYP2C19 genotypes were involved. Methods: A pre-specified subgroup analysis of a randomised controlled trial- Platelet Reactivity in Acute Non-disabling Cerebrovascular Events (PRINCE) was conducted. Patients with minor stroke or TIA were randomized for treatment with ticagrelor plus aspirin or clopidogrel plus aspirin. Platelet reactivity was assessed by Aggrestar (PL) platelet function analyzer and high on-treatment platelet reactivity (HOPR) on ticagrelor or clopidogrel was compared. Clinical outcomes included any stroke, composite vascular events and bleeding events within 90 days. Patients were categorised into carriers and non-carriers according to the carrier status of CYP2C19 LOF alleles. Results: Among 675 patients enrolled in the PRINCE trial, 387 patients were included in this subgroup: 197 were randomised to ticagrelor plus aspirin and 190 to clopidogrel plus aspirin. At 90±7 days, compared with clopidogrel/aspirin group, the proportion of HOPR in ticagrelor/aspirin group was significantly lower (19.6% versus 40.8%, P <0.001). No significant treatment-by-genotype interactions were found (P for interaction=0.12). Within 90 days, a trend towards a lower risk of new stroke in ticagrelor/aspirin compared to clopidogrel/aspirin was observed (4.6% versus 9.5%, HR 0.47, 95% CI 0.21-1.05, P=0.06). Conclusions: Ticagrelor is superior to clopidogrel in inhibiting platelet reactivity measured by the PL platelet function analyzer among patients with acute minor stroke or TIA. Our study confirmed the finding of the main analysis of PRINCE trial in a different assay. Large randomised controlled trials are needed to evaluate our findings. Clinical Trial Registration: Clinicaltrials.gov NCT02506140.